Creatio Ex Nihilo Recovered - Burrell, David B. (Modern theology, 2013)
Creatio ex nihilo sounds like a philosophical teaching, but philosophy has been utterly unprepared to offer proper expression for an origination which presupposes nothing at all! Yet each of the Abrahamic faiths insists on such an origination, so it proved serendipitous when sufficient contact opened between these diverse religious traditions to allow thinkers to assist one another in what proved to be a shared task—and indeed gain assistance from others as well, as Sara Grant elucidates the sui generis relation between creatures and creator using Shankara's "non-duality". With Robert Dobie's help, we shall can find ourselves attaining mutual illumination from witnessing Meister Eckhart and Ibn ’Arabi struggle with the same conundrum, reminding us how we will invariably falsify this crucial relating if we insist on thinking of Creator and creatures as "two things", inevitably yielding a creator who must be the "biggest of all". Yet this witness of classical explorers from different traditions may embolden contemporary thinkers to try their hand as well.